PENINGKATKAN PRESTASI BELAJAR PKn MENGGUNAKAN TEKNIK PENCATATAN MIND MAP BAGI SISWA KELAS VI B SD 1 BANTUL - Umi Fatonah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2016)
The purpose of the research was to practice the mind map writing technique in order to improve the students’ score of the six grade students of Bantul 1 Elementary School. The research involved 23 students of VB class of Bantul 1 Elementary School at the second semester in the academic year of 2014/2015. The actions of the research were done in two cycles, and each cycle consists of three stages, these were planning, implementation, observation, and reflection. The result of the research showed that the implementation of mind map writing effective and efficient to improve the score of VI class students of Bantul 1 Elementary School. The implementation of mind map writing showed; (1) students were interested to write based on their creativity in letter or picture, (2) students were able to communicate well the result of teaching and learning process, (3) students could memorize what they had learned easily.